Perbandingan Metode SAW, WP Dan TOPSIS Dalam Penentuan Guru Berprestasi - Bryan Farriq Reinaldy; Hani Sephani; Iqbal Ardiansyah; Siti Marfirah; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The determination of outstanding teachers at Mathla'ul Huda Lumpang Private Madrasah Ibtidaiyah has been carried out every year. Determination of outstanding teachers is very important to improve the quality of human resources in the progress of Mathla'ul Huda Lumpang Private Madrasah Ibtidaiyah. In this activity, the determination of outstanding teachers is still considered subjective, because it is only based on personal opinion and not based on certain criteria. The Simple Additive Weighting (SAW) method is often known as the weighted sum method. The basic concept of the Simple Additive Weighting (SAW) method is to find the weighted sum of the performance ratings for each alternative on all attributes. The Weight Product (WP) method is a decision-making method using multiplication to connect criterion values, where the value for each criterion must be raised to the first power of the criterion's weight. Meanwhile, the Technique for Order Performance of Similarity to Ideal Solution (TOPSIS) method uses the principle method that the chosen alternative must have the longest (farthest) distance from the negative ideal solution from a geometric point of view using the relative proximity of the alternatives. The three methods, namely the Order Performance of Similarity to Ideal Solution (TOPSIS) technique, Weight Product (WP) and Simple Additive Weighting (SAW) can assist in the process of determining which teachers will recommend results based on predetermined main criteria.